Grapevines grown from canes having spent 10 months in space: study of their downy mildew susceptibility - Taillis, David; Burdziej, Aleksandra; Bautista, Charlyne; Haag, Ferdinand W.M.; Lebert, Michael; Cluzet, Stéphanie (Frontiers in Astronomy and Space Sciences, 2024)
The control of plant diseases represents a significant challenge in agriculture, particularly with the current emphasis on reducing pesticide use, necessitating alternative approaches. Among them, resistant plant breeding programs offer a promising alternative. Considering the stressful conditions in space, space conditions emerge as an innovative method for advancing crop improvement. This study explored the unique potential of the International Space Station (ISS) environment to induce beneficial modifications in grapevine, resulting in plants with reduced susceptibility to diseases. Canes of two Vitis vinifera L. cultivars, Cabernet Sauvignon (CS) and Merlot (Me), have undergone a 10-month space journey on-board the ISS, while others stayed on Earth (Ground Control, GC). We conducted a 2-year analysis of the response to downy mildew (Plasmopara viticola) of plants developed from ISS and GC canes, called Mother plants. The disease development of progenies produced from Merlot Mother plants was also evaluated. A higher proportion of individuals with low-susceptibility was noted in the ISS Mother group compared to the controls for both cultivars. This trend was also observed for the Merlot progenies. Finally, 11% of Merlot individuals (Mother and progenies, and for the 2 years of study) were distributed in the low susceptibility class. This study suggests that grapevine canes exposure to ISS conditions resulted in an enhanced percentage of plants showing reduction of susceptibility to downy mildew.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Cabernet Sauvignon; ISS; Merlot; microgravity; Plasmopara viticola; radiations; space breeding; Vitis vinifera